2014
DOI: 10.1371/journal.pone.0103683
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Effects of Ethanol and Isopentenyl Pyrophosphate on Expansion of γδ T Cells in Synovial Fluid from Patients with Arthritis

Abstract: Low to moderate ethanol consumption has been associated with protective effects in autoimmune diseases such as rheumatoid arthritis, RA. An expansion of γδ T cells induced by isopentenyl pyrophosphate, IPP, likewise seems to have a protective role in arthritis. The aim of this project was to test the hypothesis that low doses of ethanol can enhance IPP-induced expansion of synovial fluid γδ T cells from patients with arthritis and may thereby potentially account for the beneficial effects of ethanol on symptom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…14 We have earlier shown that around 2.5 mM ethanol can enhance the expansion of γδ T cells stimulated with isopentenylpyrophosphate. 16 We expected to find an enhancing effect of alcohol on iso-α-acid-stimulated SH-SY5Y and NES cells, as well. Surprisingly, there was no enhancing effect in the concentration range relevant for beer drinking, and this can explain why the effects on cell expansion are similar for nonalcoholic and alcoholic beer (Figure 6).…”
Section: ■ Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…14 We have earlier shown that around 2.5 mM ethanol can enhance the expansion of γδ T cells stimulated with isopentenylpyrophosphate. 16 We expected to find an enhancing effect of alcohol on iso-α-acid-stimulated SH-SY5Y and NES cells, as well. Surprisingly, there was no enhancing effect in the concentration range relevant for beer drinking, and this can explain why the effects on cell expansion are similar for nonalcoholic and alcoholic beer (Figure 6).…”
Section: ■ Discussionsupporting
confidence: 90%
“…Thirty minutes after drinking two bottles of alcoholic beer (5.3% ABV), the blood alcohol concentration is 32 mg/100 mL, and two bottles would equal around 6–7 mM . We have earlier shown that around 2.5 mM ethanol can enhance the expansion of γδ T cells stimulated with isopentenylpyrophosphate . We expected to find an enhancing effect of alcohol on iso-α-acid-stimulated SH-SY5Y and NES cells, as well.…”
Section: Discussionmentioning
confidence: 99%
“…In a pioneering study, clones from rheumatoid synovium expressing Vγ9δ2 were shown to respond to synthetic alkyl phosphates and particularly to monoethyl phosphate (MEP) [45]. Later on, γδ T cells from synovial fluid were also shown to be reactive to isopentenyl pyrophosphate (IPP), an important endogenously produced phosphoantigen and an additive effect of a low dose of ethanol increased IPP induced proliferation of synovial γδ T cells, with similar findings applying to normal PB γδ T cells [46]. Other antigens for RA derived γδ T cells have been reported sporadically.…”
Section: Responses To Putative Antigenmentioning
confidence: 80%
“…Moreover, these expanded γδ T cells might target fibroblast-like synoviocytes, explaining the substantial protective effects of ethanol against RA and other autoimmune disorders. 139 140 In response to TCR activation, GGPP promotes cell proliferation, but its precursor, specifically farnesyl-PP, may reduce phosphorylation of p38 and ERK to regulate c-Fos-oriented DNA binding. 113 Rheumatoid fibroblastlike synoviocytes secreting pentraxin 3 and monocyte chemoattractant protein-1 respond to geranylgeranylpyrophosphate via a Rho-dependent mechanism.…”
Section: Ippmentioning
confidence: 99%
“…A substantial increase in γδ T cells in synovial fluid from arthritis patients is amplified by ethanol and isopentenyl pyrophosphate, indicating that ethanol concentrations, which further enhance IPP‐stimulated expansion of γδ T cells. Moreover, these expanded γδ T cells might target fibroblast‐like synoviocytes, explaining the substantial protective effects of ethanol against RA and other autoimmune disorders 139 …”
Section: Mevalonate Pathway and Autoimmune Diseasesmentioning
confidence: 99%